Sisters of the Undertow : A Novel - Bernhard, Johnnie, 1962- (Book collections on Project MUSE., 2020)
"Sisters Kim and Kathy Hodges are born sixteen months apart in a middle-class existence parented by Linda and David Hodges of Houston, Texas. The happy couple welcomes their "lucky daughter" Kim, who is physically and mentally advanced. Following several miscarriages, Linda delivers "unlucky" Kathy at twenty-nine weeks, ensuring a life of cognitive and physical disabilities. Kathy enters public school as a special education student, while Kim is recognized as gifted. Both sisters face life and death decisions as Houston is caught in the rip current of Hurricane Harvey. Kim learns the capricious nature of luck, while Kathy continues to make her own luck, surviving Hurricane Harvey, as she has survived all undertows with the ethereal courage of the resolute. Sisters of the Undertow examines the connotations of lucky and unlucky, the complexities of sibling rivalry, and the hand fate delivers without reason"--